2020
DOI: 10.3389/fneur.2020.611124
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of Worsening Flow Diversion Effect Due to Morphological Changes of a Stented Artery With Multiple Overlapping Stents for Partially Thrombosed Vertebral Artery Aneurysms

Abstract: Background: Morphological changes of a stented artery can cause a flow diversion effect to reduce intra-aneurysmal flow; however, there is a potential for the negative effect of increased intra-aneurysmal flow. We present cases with multiple overlapping stents for a partially thrombosed vertebral artery aneurysm and characterize the hemodynamic properties of a recurrent case by focusing on the morphological changes of the stented artery.Methods: Between October 2017 and April 2019, four consecutive cases of sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Similar findings and expectations have been suggested by Carneiro et al, according to their experience with FD and extremely large and giant intracranial aneurysms ( 35 ). Transient sac increase after flow-diversion for giant aneurysms is a well-recognized scenario ( 17 , 27 , 36 , 37 ). Post-treatment, substantial aneurysmal enlargement in our cohort occurred in nine patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings and expectations have been suggested by Carneiro et al, according to their experience with FD and extremely large and giant intracranial aneurysms ( 35 ). Transient sac increase after flow-diversion for giant aneurysms is a well-recognized scenario ( 17 , 27 , 36 , 37 ). Post-treatment, substantial aneurysmal enlargement in our cohort occurred in nine patients.…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al reported on the possibility of worsening flow diverting effects due to morphological changes in vessels with overlapping stents placed for partially thrombosed vertebral artery aneurysms using computational fluid dynamics analysis. 23) Similarly in the present case, the overlapping stents may have worsened the flow diverter effect in the vessel, resulting in residual leakage of the contrast medium outside the stent.…”
Section: Discussionmentioning
confidence: 50%
“…A total of 45 articles containing 53 patients (53 aneurysms) were identified. 347 In addition to the 53 patients identified in the literature, we also included two typical cases for illustration which were not included in the final analysis (Figures 2, 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…Giant aneurysms of the intracranial VA are rare intracranial lesions, and only 53 reported cases were identified in this review. 347 The intracranial segment of the VA runs along the anterolateral aspect of the medulla oblongata. Aneurysms originating from the intracranial segment of VA are rare and often dissecting aneurysms, 48 and most of them are stable and do not rupture.…”
Section: Discussionmentioning
confidence: 99%